Evaluation implementation of Occupational Health and Safety Based on a Management System Analysis Using Work Safety Standards According to SMK3 - Ajeng Dwi Lestari; Poppy Yaniawati; Budi Santoso (Lembaga Pengembangan Kinerja Dosen, 2025)
Occupational Safety and Health (OSH) plays a crucial role in ensuring a safe work environment, especially in high-risk sectors like healthcare, where workplace accidents and disease exposure are common. This study aims to assess the implementation of OSH at Hospital X in Bandung City by analyzing its occupational safety management system according to Government Regulation No. 50 of 2012, with a focus on Indicator 6, which pertains to Work Safety Standards under the Occupational Safety and Health Management System (SMK3). The research method used a qualitative approach supported by quantitative data, with data collection through questionnaires, observations, and interviews. The respondents included OSH management staff and hospital visitors. The study’s findings indicate that the overall implementation of Occupational Health and Safety (OHS) at Hospital X is categorized as good. This suggests that the hospital's risk control procedures are generally effective in minimizing potential workplace hazards. The hospital management’s perception of the OHS Management System (SMK3) implementation was positive, reflecting their commitment to ensuring a safe work environment. However, the assessment from visitors regarding the OSH implementation fell into the fairly good category, indicating room for improvement in certain areas, especially in terms of visitor awareness and involvement in the hospital’s safety measures. The results highlight the importance of continuous evaluation and improvement in implementing OHS standards, particularly in high-risk settings such as hospitals. Strengthening visitor education and engagement in OHS practices could further enhance the overall safety culture at the hospital. This study contributes valuable insights for improving OSH management systems and risk control strategies, ultimately aiming for a safer and healthier work environment for both hospital staff and visitors.